A Prince and a Fractured Kingdom: The Case of the Sudan’s Power Relations - Salih Mashamoun, Jihad (AUC Knowledge Fountain, 2015)
Religion has an important place in Sudanese society, and it has been used as a means of political domination. British colonialism had favored and empowered the Sufi orders of the Mahddiyya and Marghaniyya, with the result that the heads and families of those orders became the hegemonic Sufi establishment who used Sufism as a power capacity tool of political domination in the Sudan. The Sudanese Islamic/Islamist Movement (SIM), which appeared with a different religious ideology from that of the Sufi establishment, wanted to impose its ideology on the Sudanese masses. As the elites in the Sudan were fractured, allowing the SIM to impose its ideology as a means of domination, the SIM forcibly seized state power through the June 30, 1989 military coup. This capture of state power gave Al-Turabi, the head and ideologue of the SIM, the capacity to impose the SIM’s radical ideology on the Sudanese masses. Thereafter, under Al-Turabi’s leadership from the Sudan, the SIM supported likeminded radical religious movements in Eritrea and Somalia. Those countries faced their own factional conflicts for state power, which provided a great opportunity to expand the SIM ideology. While imposing the SIM ideology in and out of the Sudan, the SIM faced a power conflict within its ranks. Al-Bashir, the head of the SIM’s military faction, used military power to oust Al-Turabi from state power, resulting in the palace coup of 1999. During that coup, most members of the SIM sided with Al-Bashir. The post-Al-Turabi regime is composed of competing factions of the SIM leaders and members who sided with Al-Bashir in the palace coup, and who hold sensitive positions within the regime. Therefore, so as not to be removed from state power, Al-Bashir is in a power relation with those factions. Thus, the Sudan’s continued support for radical Islamist movements in Eritrea and Somalia after the palace coup is a byproduct of power relations within the post-Al-Turabi regime. This byproduct of power relations is a tactic conducted by Al-Bashir to discourage the competing factions within the regime from removing him from state power. It demonstrates that under Al-Bashir’s leadership, the SIM expansionist ideology, to which the competing factions remain attached, has not been abandoned.